A tensão entre filosofia e política no pensamento de Hannah Arendt - Barbosa, Willian Bento (2014)
The analysis of the conflict between philosophy and politics in the thought of Hannah Arendt was made through this thesis. The conflict expresses differences among the lifestyle dedicated to action and the way of life dedicated to contemplation, among politics and philosophy. Are these completely different activities or would be possible any relationship between them? Motivated primarily by Socrates’ judgment, the tension’s main character, Plato may have started a tradition of philosophy that would prioritize contemplation over action, a tradition broken only with Marx, Nietzsche and Kierkegaard. Such intent would have deformed both acting – dislodging it from the freedom inherent in it, as thought – displacing it from the world and the meanings to a place-none of the philosophers. In this sense, Arendt's critique of philosophy speaks to a specific way of philosophizing: the traditional metaphysical philosophy, the spirit (nous) and theory (theorein), the philosophy of professional thinkers. Arendt's reflections guide us to relocate the thought in the world and in the realm of meanings and, on the other side, to revitalize the action and freedom in its own dignity; to the passage of a philosophy of foundation to a philosophy of understanding; to a friendship in politics and to the care for the world. To illuminate the issues of the thesis, it is made necessary to establish a sort of phenomenology of the work of Arendt, a pasearse in her main works and discussions, as in the problem of action, of freedom, of thought, friendship and the political judgment.